The Use of Simile in Al-Mutanabbi’s Poem Araqqu ‘Alā Araqin Wa Mithlī Ya‘Raqu And Its Intended Function: a Study in Arabic Rhetoric (Ilm Al-Bayān) - Lilian Andriana; Rohanda Rohanda (Gunung Djati Conference Series, 2025)
This study examines the forms of tasybih (simile) found in the poem Araqqu ‘alā araqin wa mithli ya‘raqu by Al-Mutanabbi and the purposes of their usage, viewed through the lens of balaghah, specifically the branch of ‘ilm al-bayan. The poem is selected for its deep emotional expression conveyed through aesthetic and rhetorical language devices, particularly similes. The research employs a qualitative method with a descriptive-analytical approach and uses library research as the main data collection technique. The data consist of poetic lines containing elements of tasybih, which are analyzed to identify the types—such as tasybih mursal, muakkad, tamtsil, and dhamniy—and to interpret their meanings and functions within the poetic context. The results show that Al-Mutanabbi uses tasybih not only as an element of linguistic beauty but also as a means to intensify emotional expression, clarify the nature of the musyabbah, affirm qualitative meanings, and enhance the persuasive and imaginative impact of the poem. Thus, the use of tasybih in this poem demonstrates Al-Mutanabbi’s mastery in combining aesthetic power and depth of meaning through classical Arabic structures.